Production of Ethanol from Cassava and Sweet Potatoes using Yeast Extract from Palm Wine (Journal of Science and Technology, 2016)
Cassava and sweet potatoe pulps and starches have been fermented using a strain of Saccharomyces cerevisiae isolated from palm wine. Analysis of the fermented products indicated a high yield of ethanol. Comparative studies conducted using the isolated strain and a similar strain contained in Baker's Yeast showed that the former is more efficient in fermenting blackstrap molasses than the latter.